Implementation of Tax Incentive for Micro, Small, and Medium Enterprises at Special Economic Zone in Indonesia - Kaharuddin, Kaharuddin; Minollah, Minollah; Cahyowati, RR.; Nurbani, Erlies Septiana (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
Implementing tax incentives for micro, small, and medium-sized enterprises (MSMis) is an important strategy in supporting economic growth, especially in developing regions. The study focuses on the application of tax incentives in the Mandalika Special Economic Area, Central Lombok Regency as a one of represtative of special economic zone ini Indonesia, designed to strengthen the local MSMEs sector. The study aims to assess the effectiveness of tax incentives given to MSMEs to support business development and improved economic well-being in the region. Interviews with stakeholders, such as MSMEs entrepreneurs, government officials, and taxpayers, form the basis of the methodology. In addition, the study also examines secondary data from financial reports and relevant economic statistics. The research findings show that the implementation of tax incentives in the Mandalika Special Economic Zone has had a positive impact on MSMEs growth, increased capital accessibility, and expanded local enterprises' market share. However, it is needed to address some challenges in understanding incentive policies and administrative procedures. To maximize benefits for MSMEs, the study recommends increased socialization and training on tax incentives, as well as simplification of administrative processes. Thus, it is expected that tax incentives can be more effective in boosting economic growth in the Mandalika Special Economic Zone and contribute significantly to regional economic development.